Действие эпихлоргидрина на состояние желудка крыс и коррекция возникших изменений экстрактом эхинацеи пурпурной - Смирнов, С.Н.; Кувенёва, М.Л.; Смирнов, А.С.; Росомахина, О.М.; Власенко, И.М. (Таврический медико-биологический вестник, 2013)
Було вивчено зміни морфофункціонального стану шлунку щурів під впливом епіхлоргідрину (ЕХГ) та їх корекція екстрактом ехінацеї пурпурної (ЕЕП).Досліди проводили на статевозрілих безпородних білих щурах- самцях. Забір шлункового соку і зіскрібок із слизової оболонки шлунку робили на 1‑у, 30‑у і 60‑у добу після завершення екзогенної дії. Визначалася протеолітична активність шлункового соку, робився цитологічний аналіз зіскрібка із слизової оболонки шлунку.ЕХГ впливає на протеолітичну активність шлункового соку і клітинний склад зіскрібка із слизової оболонки шлунку. Застосування ЕЕП зменшує ступінь цих змін. Подальші дослідження змін протеолітичної активності шлункового соку, а також цитологічний аналіз зіскрібка із слизовою оболонкою шлунку під впливом ксенобіотиків дозволять розширити уявлення про закономірності їх дії на стан шлунку. It was studied of changes of the morphofunctional state of stomach of rats under action of epichlorohydrin (ECH) and their correction by the extract of Echinacea purple (EEP). Research was carried out on mature outbred white rats-males. The fence of gastric juice and scraping from the mucous membrane of stomach were produced on 1th, 30th and 60th days after completion of exogenous influence proteolytic activity of gastric juice was determined, the cytological composition of scrape from the mucous of stomach was produced of stomach.ECH has influence on proteolytic activity of gastric juice and cellular composition of scrape from the mucous membrane of stomach. Application of EEP diminishes the degree of these changes.Further researches of changes of proteolytic activity of gastric juice, and also cytological analysis of scrape with the mucous membrane of stomach under influence of xenobiotics will allow to extend notions about regularities of their action on the state of stomach.